Evaluation of Antidepressant and Anxiolytic Activity of Fruit Extract of Hylocereus undatus in Experimental Animals (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Hylocereus undatus, generally known as dragon fruit was used in the present study to investigate antidepressant and anti-anxiety activity. In antidepressant activity we found that administration of 200 mg/kg and 400 mg/kg ethanolic fruit extract of Hylocereus undatus (EFEHU) and standard drug imipramine (20 mg/kg) for 21 days to respective group of animals they showed significantly reduced the immobility time in both Tail suspension test (TST) and Despair swim test (DST) in dose dependent manner as well as biochemical estimation was done. In anxiolytic activity administration of 200 mg/kg and 400 mg/kg EFEHU and standard drug diazepam (2 mg/kg) for 14 days to respective group of animals. In Elevated plus maze test (EPMT) significantly increased time spent in open arm and number of entries in open arm. The significantly increased level of 5-HT and GABA in brain of mice in dose dependent manner in both DST and EPMT. The phytochemical study of EFEHU showed the presence of alkaloids, tannins, carbohydrates, flavonoids, terpenoids, saponins, oils, phenolic compounds and qualitative examination by HPTLC technique showed that presence of quercetin and gallic acid. Therefore, the presence of such compounds in the extract may be responsible for the antidepressant and anxiolytic activity. Therefore, present study validates its antidepressant and anxiolytic activity. Further, research is required to elucidate its specific mechanism of action and isolation of responsible active principles.